L. Yuqun (2017). Traditional Chinese medicine: Understanding its principles and practices (Trads. L. Zhaoguo, W. Laping y L. Xiru). Beijing: China Intercontinental Press. 131 pp. - Incaurgarat, María Florencia (Estudios de Asia y África, 2019)
L. Yuqun (2017). Traditional Chinese medicine: Understanding its principles and practices (Trads. L. Zhaoguo, W. Laping y L. Xiru). Beijing: China Intercontinental Press. 131 pp.